The limitation of policies regarding Sportstoto: Focusing on illegal sports betting and government sports budget issues - Taeksoo Chun (Korea Institute of Sport Science, 2020)
Purpose This study focused on analyzing the policies regarding operation of Sportstoto, a sole legal sports betting business in Korea. Methods In order to fulfill the research goal, literature review on reports, articles, and statistics from Ministry of Culture, Sports and Tourism, National Gambling Control Commission, Korean Sports Promotion Foundation, and other precedent studies was conducted. Results Currently Sportstoto fails to maintain its competitiveness due to inconvenient betting process, lack of product diversification, and low payout rate, resulting in the growth of illegal sports gambling. In addition, governmental aid for sports budget has diminished consistently, while at the same time the revenue cap regulation for betting industry restrains the development of Sportstoto and disturbs the gathering of sports budget, which appears to be a policy contradiction. Moreover, there are no specific guidelines for the expenditure of Sportstoto revenue which function as a budget. Conclusions This study suggests three ideas to overcome these problems. First is the alleviation of regulation in non-monetary area so that Sportstoto can improve its competitiveness against illegal sports gambling. Second is the clear establishment of policy regarding sports budget, either to foster Sportstoto as a fundraising business, or to enlarge governmental allocation for the budget. Lastly, institutional management must be provided for the expenditure of Sportstoto revenue as to follow government's sports policies.